Analisis Faktor-Faktor yang Mempengaruhi Pengangguran (Studi Kasus: 11 Provinsi di Indonesia Periode 2006-2015) - Saputri, Shela Nindya (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This research aims to determine the factors that influence unemployment. Variables used in this research is economic growth, domestic investment, pma, inflation, and umk. The research method in this study is panel regression. The results of this research are economic growth and umk have relationship the negative effect and sinifikan against unemployment. As for inflation, pmdn, and pma has a positive and significant impact on unemployment.Keywords: economic growth, inflation, pmdn, pma, and umk